Decentralized consensus protocols: possibilities and recommendations for use - Isirova, K.V.; Potii, O.V. (Radiotekhnika, 2018)
Centralised systems development problematic issues are described. Decentralized systems development including for critical infrastructures is proposed. Existing decentralized consensus protocols comparative analysis is carried out and recommendations for their use are proposed.